Potential Barriers in Implementing Local-Food-Based Complementary Feeding Practice (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2021)
Local-food-based complementary feeding (LFBCF) practice may be an important approach in the growth and development of children aged 6 to 24 months. This study aimed to describe potential barriers in implementing local food-based complementary feeding practices among mothers in Banyuasin regency, Indonesia. A qualitative study was conducted by using 24 semi-structured interviews and a focus group discussion. Participants were 24 mothers with children aged 6 to 24 months in Banyuasin Regency, Indonesia that recruited purposively. Data were analyzed using thematic analysis. The majority of the mothers were 20-30 years old. All participants have implemented LFBCF practice because local food ingredients are easy to find locally at an affordable price. Community cadres assisted village midwives in integrated health post service such as disseminating information concerning local food recipes and facilitating information exchange among mothers regarding complementary feeding practice. Three main emerged themes identified from this study were: mother's knowledge about local food recipes, mother's knowledge about healthy complementary food preparation, child-eating behavior. Improving the nutritional status of children starts with the family by motivating mothers to provide complementary foods, which also requires the support of local cadres.